Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Solve the equation: (12x-1)(6x-1)(4x-1)(3x-1) = 5

Solve the equation:                       (12x-1)(6x-1)(4x-1)(3x-1) = 5

Grade:12

1 Answers

SHAIK AASIF AHAMED
askIITians Faculty 74 Points
6 years ago
Hello student,
Given eqn can be written as
(x-1/12)(x-1/6)(x-1/4)(x-1/3)=(5/12*4*6*3)..................(1)
let y=1/4[(x-1/12)+(x-1/6)+(x-1/4)+(x-1/3)]
so y=x-5/24...............(2)
Substituting 2 in 1 we get
(y+1/24)(y-1/24)(y+3/24)(y-3/24)=(5/12*4*6*3)
after simplifying and putting y2-5/242=t we get
(t+4/242)(t-4/242)=(121/1442)
t2=(16/244)+(121/1442)
t=11/144
y=\pm7/24
we get x=1/2,-1/12
Thanks and Regards
Shaik Aasif
askIItians faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free